“The Simple Magic of Life”: Phenomenology, Ontology, and Animal Ethics - Weisberg, Zipporah (Humanimalia, 2015)
This paper explores the important contribution phenomenology can make to animal ethics. The underlying assumption is that animal ethics is as strong as the conception of animal ontology it takes for granted. I contend that Peter Singer’s reductive ontology of animals as suffering beings leads him astray not least because it prevents him from opposing killing animals as a matter of principle. Other leading ethicists such as Martha Nussbaum and Tom Regan offer more nuanced accounts of animal ontology and correspondingly richer theories of justice and rights, but they do not go far enough. Nussbaum even contradicts her own theory of capabilities by also refusing to refuse killing. Marc Bekoff, Jonathan Balcombe, and other ethologists, on the other hand, do a marvellous job of filling in the gaps in our understanding of the complexity of animals’ emotional, social, and moral lives. Not surprisingly, as a result of their insights into animal ontology, they categorically reject killing animals and advocate for the total transformation of their conditions of existence. Maurice Merleau-Ponty's phenomenology of embodiment, I suggest here offers another crucial inroad into a more meaningful and robust animal ethics by illuminating the complex perceptual dimensions of animal subjectivity.